A Decision Analysis Approach for Unique Situation Competitive Bidding - BUNN, Derek (Institutional Knowledge at Singapore Management University, 1976)
Looks at the competitive bidding situation in a single occasion context. Provides a "thinking algorithm" model based on decision analysis which requires the decision maker to make subjective assessments of uncertain quantities. Uses the case study of a tender of unpounded butter offered to J. Sainbury Ltd to consider aspects of the relevant theory of competitive bidding.